2010
DOI: 10.1108/17505931011092817
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mediated power asymmetry, relational risk perception, and governance mechanism in new product development relationships

Abstract: Purpose -The purpose of this paper is to examine the impact of mediated power asymmetry on relational risk perception and modes of governance mechanism (intention-based trust and unilateral control). Design/methodology/approach -Survey research was conducted to collect data from 112 new product development (NPD) relationships and structural equation modeling was conducted to test the hypotheses. Findings -The results suggest that benefiting from mediated power asymmetries by a firm is positively related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 93 publications
(113 reference statements)
0
20
0
Order By: Relevance
“…Therefore, reward power indeed operates differently from coercive power when applied to supplier relationship management. Reward and coercive powers should therefore not be simply bundled together as mediated powers, as have been done before (e.g., Brown et al., ; Dapiran & Hogarth‐Scott, ; Handley & Benton, ; Ke et al., ; Teimoury et al., ). Reward power, as a form of positive feedback to the supplier, promotes a sense of competence and enhances the supplier's motivation to commit to the relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, reward power indeed operates differently from coercive power when applied to supplier relationship management. Reward and coercive powers should therefore not be simply bundled together as mediated powers, as have been done before (e.g., Brown et al., ; Dapiran & Hogarth‐Scott, ; Handley & Benton, ; Ke et al., ; Teimoury et al., ). Reward power, as a form of positive feedback to the supplier, promotes a sense of competence and enhances the supplier's motivation to commit to the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, empirical findings about the roles of reward and coercive powers in buyer–supplier relationships have been mixed. On the one hand, there have been studies showing negative effects of mediated powers on buyer–supplier relationships (e.g., Brown et al., ; Dapiran & Hogarth‐Scott, ; Handley & Benton, ; Ke et al., ; Teimoury, Fesharaki & Bazyar, ). Conversely, other researchers have found contrasting or insignificant effects of reward and coercive powers on buyer–supplier relationships (e.g., Benton & Maloni, ; Maloni & Benton, ; Terpend & Ashenbaum, ; Zhao et al., ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For this reason, rather than considering the concepts involved in the research (value and risk perceptions) from the product perspective, we aimed to address them from the perspective of interviewed consumers. Accordingly, products that could generate extreme behaviors were excluded, as such behaviors could affect the results of the survey; for example, a product with a high perceived financial risk would tend to be associated with weaker purchase intentions regardless of whether a sales promotion was applied (Chanvarasuth, Sarin, & Sego, 2002;Teimoury, Fesharaki, & Bazyar, 2010).…”
Section: Exploratory and Descriptive Stagesmentioning
confidence: 99%
“…For example, Hsieh et al (2010) explored how relational conditions affect the governance mechanism through perceived risks after international joint venture formations. Moreover, Teimoury et al (2010) studied the effects of mediated power on the use of intention-based trust and unilateral control governance mechanisms through perceived risks. However, although Das and Teng (2004) reiterated the need to explore the integrated connections among trust, perceived risks, and behavior (i.e., contract enforcement in this article), it still requires significant research attention.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…Furthermore, we also attempted to determine the mediating mechanism between trust and contract enforcement. As Teimoury et al (2010) revealed, the management of risk should be properly understood to explore governance thoroughly. Thus, we argue that contract enforcement, as a part of governance, is closely associated with perceived risk.…”
Section: Introductionmentioning
confidence: 99%